Bats Are an Untapped System for Understanding Microbiome Evolution in Mammals - Melissa R. Ingala (American Society for Microbiology, 2018)
ABSTRACT Mammals evolved in a microbial world, and consequently, microbial symbionts have played a role in their evolution. An exciting new subdiscipline of metagenomics considers the ways in which microbes, particularly those found in the gut, have facilitated the ecological and phylogenetic radiation of mammals. However, the vast majority of such studies focus on domestic animals, laboratory models, or charismatic megafauna (e.g., pandas and chimpanzees). The result is a plethora of studies covering few taxa across the mammal tree of life, leaving broad patterns of microbiome function and evolution unclear. Wildlife microbiome research urgently needs a model system in which to test hypotheses about metagenomic involvement in host ecology and evolution. We propose that bats (Order: Chiroptera) represent a model system ideal for comparative microbiome research, affording opportunities to examine host phylogeny, diet, and other natural history characteristics in relation to the evolution of the gut microbiome.